Rozwój i pomiar kapitału intelektualnego - Skrzypek, Elżbieta (Developing and Measuring Intellectual Capital, 2008)
Knowledge society highly values intellectual capital and knowledge for which success of businesses and individuals alike rest upon quality and efficiency of intellectual capital developed and applied. Intellectual capital is fundamental for business value, innovations applied and supplied and firm's potential competitive advantage. Measuring intellectual capital is indispensable with respect to well grounded methods as is seeking new ways of developing and improving intellectual capital resources. Conclusions for business leaders are that intellectual capital must be properly addressed and measured and managed. Several examples of widely accepted methods of measuring intellectual capital are presented. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 251-265